FIRST UK EXPERIENCE WITH NAVIGATED TRANSCRANIAL MAGNETIC STIMULATION IN PRE-SURGICAL MAPPING. (3rd October 2018) - Jung, Josephine; Lavrador, José Pedro; Patel, Sabina; Lam, Jordan; Giamouriadis, Anastasios; Bhangoo, Ranj; Vergani, Francesco
Abstract: OBJECTIVES: Surgery for lesions in eloquent brain areas is challenging due to the underlying risk of causing permanent neurological deficits. To date, Direct Cortical Stimulation (DCS) and intra-operative neuro-monitoring (IOM) represent the gold standard in minimising such risk. Recently, Transcranial Magnetic Stimulation (TMS) has emerged as a mapping tool that assists in optimising surgical planning. The aim of this study is to validate our TMS findings against DCS. METHODS: Retrospective single-centre analysis of 35 adult patients with TMS, DCS and IOM for space occupying lesion (SOL) at King's College Hospital from February 2017 to February 2018. Patients with arteriovenous malformation were excluded from analysis. We collected data on patient demographics, tumour entity/location, extent of resection (EoR), change of surgical strategy, neurological outcome, and correlated TMS with DCS/IOM. RESULTS: 24/35 patients (68.6%) had pre-operative motor mapping and 11/35 (31.4%) were mapped for language. Histopathology demonstrated a glioma in 85.7% of patients (high grade n=24; low grade n=6) and metastasis (n=2), cavernoma (n=1) and other cases (n=2). TMS resulted in a change of surgical strategy in 34.3% (craniotomy size n=7; surgical pathway n=3; EoR n=1; surgical indication n=1). Sensitivity of TMS for language was 70.6% with a positive predictive value of 60.0% (n=9). TMS motor mapping correlated with DCS/IOM in all cases with snapshot hotspot conformity of 100% (n=5). A total of 12 patients had a new transient neurological deficit which resolved/significantly improved except for one case (expressive dysphasia). CONCLUSIONS: TMS is a non-invasive, safe and effective adjunct in surgery planning in eloquent brain areas. It is reliable in predicting M1/motor mapping and shows promising results for language mapping. Larger randomised controlled trials are needed to validate these findings.